JATUHNYA THALAQ PERSFEKTIF IMAM SYAFI’I DAN IMAM MALIKI - Marbujang (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2025)
This research seeks to explore of thalaq within the Syafi‘i and Maliki schools through a comparative lens, aiming to uncover their shared principles, methodological differences, and contemporary relevance for family law reform. The results indicate that both the Syafi‘i and Maliki traditions are grounded in the same foundational legal authorities—the Qur’an, the Sunnah, and ijma‘ and exhibit parallel structures in their classification of thalaq as well as in their treatment of iddah and ruju‘. However, clear divergences arise in their methodological frameworks. The Syafi‘i school maintains a predominantly textual and literal orientation, while the Maliki school places greater emphasis on contextual considerations through the use of ‘amal ahl al-Madinah and the principle of maslahah mursalah. These contrasting approaches produce differing legal assessments concerning divorce pronounced in anger, the validity of triple thalaq, and the extent to which intention determines the legal consequences of a divorce pronouncement.